2022
DOI: 10.1111/jfpp.16336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different types and concentrations of salts added toRequesoncheese on texture, sensory, and physiochemical characteristics

Abstract: Different salts and concentrations (1% NaCl, 1.5% NaCl, 1% (1:1) NaCl/KCl, 1.5% (1:1) NaCl/KCl, and 0.1% CaCl2) were used to elaborate Requeson cheese to evaluate yield, color, texture, physiochemical composition, and sensory characteristics. Yield, moisture, and protein content did not change among treatments (p > .05). Fat content was higher (p < .05) in the cheese without added salt. Adhesiveness was greater (p < .05) in cheese with 0.1% CaCl2 and lowest in cheese without added salt. The a* value presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Experimental design contemplated a factorial treatment arrangement, in a completely randomized design and considering the following factors: four salt levels/combination; control (requeson cheese without salt), requeson cheese with 1% NaCl, 1.5% NaCl and 1.5% (1:1) of NaCl/KCl, two packing types: ordinary retail packaging in a low-density polyethylene bag and a vacuum packaging in a polyethylene/polyamide bag. The percentages and combinations of the salts used to elaborate the requeson cheese treatments were chosen according to a previous study, where these were the most sensory accepted by consumers [28].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental design contemplated a factorial treatment arrangement, in a completely randomized design and considering the following factors: four salt levels/combination; control (requeson cheese without salt), requeson cheese with 1% NaCl, 1.5% NaCl and 1.5% (1:1) of NaCl/KCl, two packing types: ordinary retail packaging in a low-density polyethylene bag and a vacuum packaging in a polyethylene/polyamide bag. The percentages and combinations of the salts used to elaborate the requeson cheese treatments were chosen according to a previous study, where these were the most sensory accepted by consumers [28].…”
Section: Experimental Designmentioning
confidence: 99%
“…All analyses were carried out in triplicate. Physicochemical composition, texture and sensory analysis of treatments have been reported previously [28].…”
Section: Experimental Designmentioning
confidence: 99%
“…Nevertheless, decreasing the salt concentration directly may raise the safety problematic and affect the food sensory properties (such as taste and odor) (Chun et al, 2020; Wolkers‐Rooijackers et al, 2013). In recent years, more and more attention has been paid to NaCl substitutes, among which potassium chloride (KCl) is regarded as an ideal and promising substitute (Ramírez‐Rivas et al, 2022). A study has shown that lowering sodium by compensating with potassium in diet will avoid deaths of tens of thousands of people in north China every year (Neal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to NaCl substitutes, among which potassium chloride (KCl) is regarded as an ideal and promising substitute (Ramírez-Rivas et al, 2022). A study has shown that lowering sodium by compensating with potassium in diet will avoid deaths of tens of thousands of people in north China every year (Neal et al, 2021).…”
mentioning
confidence: 99%